HOUSEHOLDERS’ SATISFACTION TOWARDS SOLID WASTE COLLECTION SERVICES OF ZOOMLION GHANA LTD IN WA, GHANA - Akaateba, Millicent Awialie; Yakubu, Ibrahim (European Scientific Journal, ESJ, 2013)
Solid waste management remains a major challenge to most governments in developing countries in view of the increasing volumes of waste materials generated and disposed to the environment in urban areas. As a result, many governments have embraced public-private partnerships to improve the effectiveness and efficiency in the delivery of waste management services. This study used a cross-sectional household survey to investigate householders’ satisfaction with solid waste collection services provided by Zoomlion Ghana Ltd in the Wa Municipality. A total of 193 householders were selected through simple random sampling from registered household clients of Zoomlion Ghana Ltd in the Wa Municipality. The results of the study revealed that householders were ‘moderately satisfied’ with most waste management services delivered by the Company indicating an acceptable level of service delivery. The one-way ANOVA results showed significant differences in householders’ satisfaction by income level and house type for service delivery dimensions on frequency of waste collection; handling of waste during transport and disposal; and household education on waste management. The study posits that although the services delivered by the company can be considered as acceptable, much improvement could be made by simply addressing issues on household education, prompt response to user complains and ensuring effective monitoring and sanctioning by the Municipal Assembly. This will enable Zoomlion Ghana Ltd deliver quality services to its clients.